إنشاء خرائط رقمية لحالة الرصف الطرقي على طريق طرطوس- صافيتا - كنعان, فادي; أسعد, شذى; محمود, مجد (Latakia University Journal -Engineering Sciences Series, 2019)
This research highlighted the vital role of Pavement Management Systems integrating with Geographic Information Systems in planning and managing road maintenance in Tartous in order to reach better conditions of safety and comfort on roads . This study included the proposal experimental study for the management of pavement maintenance over a road following The General Establishment for Road Communications – Tartous branch , This road was divided to links and segments then evaluated using the " pavement condition index" (pci ) on this sections which gave us a numeric pointer leading in turn to the type of maintenance needed for the particular pavement . In this study we depended on the Geographic Information Systems to design and build a comprehensive database linked to the digitized map of the studied roads إنشاء خرائط رقمية لحالة الرصف الطرقي على طريق طرطوس- صافيتا يبرز من خلال هذا البحث الدور الحيوي الذي تلعبه نظم إدارة الرصف الطرقي بالتكامل مع نظم المعلومات الجغرافية في تخطيط وإدارة الصيانة الطرقية في محافظة طرطوس, مما يؤدي إلى رفع سوية الأداء والوصول إلى شروط أفضل من الراحة والأمان لمستخدمي الطرق. تتضمن هذه الدراسة اقتراح دراسة لإدارة صيانة الرصف لإحدى الطرق التابعة للمؤسسة العامة للمواصلات الطرقية في فرع طرطوس, حيث تم تقسيم الطريق المدروس إلى وصلات وقطاعات, و تمت عملية تقييم حالة سطح الرصف له بالاعتماد على طريقة معامل حاله الرصف( pavement condition index) (PCI) التي توصلنا بموجبه إلى مؤشر رقمي عن حالة الرصف على هذه القطاعات, مما أعطى مؤشرات لطريقة الصيانة اللازمة للرصف. اعتمدت هذه الدراسة على نظم المعلومات الجغرافية (GIS) (Geographic Information Systems )في تصميم وبناء قاعدة بيانات فاعلة خاصة بالطريق قيد الدراسة وربطه بالخريطة الرقمية الخاصة به.